2008
DOI: 10.1083/jcb.200707022
|View full text |Cite
|
Sign up to set email alerts
|

Kank regulates RhoA-dependent formation of actin stress fibers and cell migration via 14-3-3 in PI3K–Akt signaling

Abstract: Phosphoinositide-3 kinase (PI3K)/Akt signaling is activated by growth factors such as insulin and epidermal growth factor (EGF) and regulates several functions such as cell cycling, apoptosis, cell growth, and cell migration. Here, we find that Kank is an Akt substrate located downstream of PI3K and a 14-3-3–binding protein. The interaction between Kank and 14-3-3 is regulated by insulin and EGF and is mediated through phosphorylation of Kank by Akt. In NIH3T3 cells expressing Kank, the amount of actin stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 60 publications
5
108
0
Order By: Relevance
“…Other 14-3-3 family members were shown previously to regulate intermediate filament architecture by functioning as K8/K18 solubility cofactors in a PKCζ-dependent mechanism (40)(41)(42). In addition, a number of studies have highlighted different mechanisms by which 14-3-3 family members regulate actin dynamics either through stabilizing cofilin phosphorylation or by inhibiting signals through the AKT-RhoA pathway (12,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Other 14-3-3 family members were shown previously to regulate intermediate filament architecture by functioning as K8/K18 solubility cofactors in a PKCζ-dependent mechanism (40)(41)(42). In addition, a number of studies have highlighted different mechanisms by which 14-3-3 family members regulate actin dynamics either through stabilizing cofilin phosphorylation or by inhibiting signals through the AKT-RhoA pathway (12,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…40 This stimulates the formation of actin stress fibers through the activation of RhoA. 41 Therefore, PI3K signaling evoked by truncated Tie2 ( Figure 5) may be involved in the formation of actin stress fibers in endothelial cells ( Figure 6A), leading to endothelial cell retraction. Third, when epithinexpressing cells escape the vasculature, the matrix-degrading activity of epithin 19 can generate a pathway for the cells to invade further into the layers of the extracellular matrix.…”
Section: Roles Of Epithin-mediated Tie2 Regulation In Transendotheliamentioning
confidence: 99%
“…Recently, we found that liprin-b1 interacts with KANK1 (van der Vaart et al, 2013), one of the four members of the KANK family of proteins, which were proposed to act as tumor suppressors and regulators of cell polarity and migration through Rho GTPase signaling (Gee et al, 2015;Kakinuma et al, 2008Li et al, 2011;Roy et al, 2009). KANK1 recruits the kinesin-4 KIF21A to CMSCs, which inhibits microtubule polymerization and prevents microtubule overgrowth at the cell edge van der Vaart et al, 2013).…”
Section: Introductionmentioning
confidence: 99%